Importance of Continuous Pulse Oximetry of the Ipsilateral Thumb/Index Finger during Transradial Angiography. (11th December 2011) - Puffer, Ross C.; Kallmes, David F.
Abstract : We present a case of a 63-year-old male undergoing attempted basilar artery embolization using a right transradial artery approach in which continuous pulse oximetry of the ipsilateral thumb uncovered unanticipated hand ischemia during the procedure. A preprocedural evaluation using pulse oximetry of the right thumb demonstrated normal waveform and maintenance of normal oxygen saturation during manual compression of the right radial artery. This normal waveform and oxygen saturation was maintained after insertion of a 6Fr sheath into the radial artery. After insertion of a 6Fr guiding catheter into the right vertebral artery, near-complete dampening of the pulse oximetry waveform and precipitous decline in oxygen saturation were noted. Examination of the right hand demonstrated poor tissue perfusion. Immediate removal of the guiding catheter led to return of a normal waveform, oxygen saturation, and tissue perfusion. This case demonstrates the importance of continuous, intraprocedural monitoring of oxygenation of the ipsilateral hand during transradial angiography in order to avoid unanticipated perfusion abnormalities.